Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2001
DOI: 10.1381/096089201321209468
|View full text |Cite
|
Sign up to set email alerts
|

The BioEnterics Intragastric Balloon (BIB): How to Use it

Abstract: The device, supported by a competent motivated team, is another modality available for weight loss.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(22 citation statements)
references
References 2 publications
0
19
0
2
Order By: Relevance
“…A randomized study has shown that a double-channel endoscope was superior to a single-channel endoscope in terms of number of lost balloons, balloon retrieval duration, and patient discomfort (the BIB was seized with both grasping forceps and a snare) [16]. However, in the present author's experience, the use of dedicated ancillary devices to fully empty and then grasp the balloon consistently allows BIB removal, even with a single-channel endoscope [33]. Nonetheless, a double-channel endoscope may be useful because gastric content may be abundant even if a liquid diet has been prescribed for the 24 h preceding BIB removal.…”
Section: Practical Considerationsmentioning
confidence: 65%
See 1 more Smart Citation
“…A randomized study has shown that a double-channel endoscope was superior to a single-channel endoscope in terms of number of lost balloons, balloon retrieval duration, and patient discomfort (the BIB was seized with both grasping forceps and a snare) [16]. However, in the present author's experience, the use of dedicated ancillary devices to fully empty and then grasp the balloon consistently allows BIB removal, even with a single-channel endoscope [33]. Nonetheless, a double-channel endoscope may be useful because gastric content may be abundant even if a liquid diet has been prescribed for the 24 h preceding BIB removal.…”
Section: Practical Considerationsmentioning
confidence: 65%
“…Balloon removal requires specific material that should be available as soon as a program of BIB therapy is started [33]. A randomized study has shown that a double-channel endoscope was superior to a single-channel endoscope in terms of number of lost balloons, balloon retrieval duration, and patient discomfort (the BIB was seized with both grasping forceps and a snare) [16].…”
Section: Practical Considerationsmentioning
confidence: 99%
“…La implantación del BIB vía endoscópica se realizó en quirófano bajo anestesia general e intubación orotraqueal (16). El BIB fue llenado de forma estándar con 500 cc de suero salino mezclado con 10 ml de azul de metileno para detectar precozmente una fuga mediante la coloración de la orina del paciente (17).…”
Section: Materials Y Métodosunclassified
“…Whether managed by diets, exercise and medication, or endoscopic and surgical interventions, the treatment of obesity aims to reduce weight and the risks of comorbidities [2]. Temporary intragastric balloon application together with a diet program has gained popularity [3,4]. This clinical prospective study has been designed to evaluate the effects of intragastric balloon application on obese patients.…”
Section: Introductionmentioning
confidence: 99%